2010
DOI: 10.1086/656235
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Pegylated Interferon plus Ribavirin byIL28BGene Variation in Patients Coinfected with HIV and Hepatitis C Virus

Abstract: IL28B gene variations independently predict SVR in HIV/HCV-coinfected patients with HCV genotype 1 and non-genotype 1 HCV infection. The association between rs12979860 and plasma low-density lipoprotein cholesterol suggests that the system low-density lipoprotein ligand/receptor might be involved in the effect of this genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 22 publications
10
72
1
Order By: Relevance
“…For subtype 1b, oligonucleotides HCVproL2 (sense, 5Ј-GGGTTGAATTCTAT GGCTCCTATTGGATCTGTTGTTATTGTTGGAAGAATTATTTTGTCTG GAAGAGGAGGACCTATCACGGCCTACTCCCAA-3Ј, residues 3414 to 3434 of the HCV-J strain) and HCVproR (antisense, 5Ј-GGGAGGGGCTCG AGTCAAGACCGCATAGTAGTTTCCAT-3Ј, residues 3933 to 3952 of the HCV-J strain) were used. The PCR products were digested with EcoRI and XhoI and ligated to pBSK (Stratagene) to generate a ␤-gal-HCV NS3 2-181 /4 [21][22][23][24][25][26][27][28][29][30][31][32][33][34] protease fusion protein (pHCVNS3 2-181 /4 21-34 protease). To ensure that multiple NS3/4 protease templates were present in each quasispecies that was analyzed, four different PCR amplifications were performed for each sample and pooled before cloning.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…For subtype 1b, oligonucleotides HCVproL2 (sense, 5Ј-GGGTTGAATTCTAT GGCTCCTATTGGATCTGTTGTTATTGTTGGAAGAATTATTTTGTCTG GAAGAGGAGGACCTATCACGGCCTACTCCCAA-3Ј, residues 3414 to 3434 of the HCV-J strain) and HCVproR (antisense, 5Ј-GGGAGGGGCTCG AGTCAAGACCGCATAGTAGTTTCCAT-3Ј, residues 3933 to 3952 of the HCV-J strain) were used. The PCR products were digested with EcoRI and XhoI and ligated to pBSK (Stratagene) to generate a ␤-gal-HCV NS3 2-181 /4 [21][22][23][24][25][26][27][28][29][30][31][32][33][34] protease fusion protein (pHCVNS3 2-181 /4 21-34 protease). To ensure that multiple NS3/4 protease templates were present in each quasispecies that was analyzed, four different PCR amplifications were performed for each sample and pooled before cloning.…”
Section: Patientsmentioning
confidence: 99%
“…The resulting PCR products were digested with NsiI and HindIII and ligated to pcI.HCVNS4B/NS5Acro previously digested with NsiI and HindIII. Escherichia coli JM109 cells containing plasmid pcI.Cardifcro were then transformed with plasmid pHCVNS3 2-181 /4 [21][22][23][24][25][26][27][28][29][30][31][32][33][34] protease. Transformed cells were grown overnight at 30°C in the presence of 0.2% maltose-12.5 g/ml of tetracycline-20 g/ml of ampicillin, harvested by centrifugation, and resuspended to an optical density at 600 nm of 2.0/ml in 10 mM MgSO 4 .…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide association studies have identified several single nucleotide polymorphisms (SNPs) around the IL28B gene (which codes for IFN-lambda 3) which are strongly associated with treatment induced viral clearance of genotype 1 infection in HIV/HCV coinfected patients (i.e. IL28B genotype CC) [120,121]. IL28B TT/CT genotypes are associated with poorer response to IFN based treatment.…”
Section: Predicting Ifn Response -Il28bmentioning
confidence: 99%
“…35,49 In patients with recurrent HCV after orthotopic liver transplantation, IL28B polymorphisms allow prediction of SVR to PEG-IFN/RBV therapy. 50,51 The value of IL28B polymorphisms have also been shown to predict response to triple therapy, including the directly acting antiviral drug telaprevir along with PEG-IFN/RBV.…”
Section: Other Emerging Data Of Interleukin 28b Polymorphisms and Hepmentioning
confidence: 99%